2016
DOI: 10.3390/su8050463
|View full text |Cite
|
Sign up to set email alerts
|

System Merits or Failures? Policies for Transition to Sustainable P and N Systems in The Netherlands and Finland

Abstract: Nitrogen (N) and phosphorus (P) cycles are absolutely vital in maintaining sustainable food systems. Human activities disturb the natural balance of these cycles by creating enormous additional nutrient fluxes, causing eutrophication of waterways and pollution in land systems. To tackle this problem, sustainable nutrient management is required. This paper addresses sustainable nutrient management in two countries: The Netherlands and Finland. We adopt a critical perspective on resource politics, especially tow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 47 publications
(48 reference statements)
0
11
0
Order By: Relevance
“…All four food security dimensions are considered Source: Adapted from Garnett (2014) (Sixt et al 2018), as well as the waterenergy-food nexus (Halbe et al 2015). In other cases, the focus is on transitions in the use of some agricultural inputs, such as fertilisers (Hoppe et al 2016;Jacobs et al 2017) and pesticides (Hammond Wagner et al, 2016;Sherwood and Paredes 2014).…”
Section: Topical Focus Of Research On Agro-food Sustainability Transimentioning
confidence: 99%
“…All four food security dimensions are considered Source: Adapted from Garnett (2014) (Sixt et al 2018), as well as the waterenergy-food nexus (Halbe et al 2015). In other cases, the focus is on transitions in the use of some agricultural inputs, such as fertilisers (Hoppe et al 2016;Jacobs et al 2017) and pesticides (Hammond Wagner et al, 2016;Sherwood and Paredes 2014).…”
Section: Topical Focus Of Research On Agro-food Sustainability Transimentioning
confidence: 99%
“…In fact, papers focus on building visions for sustainable agro-food systems and actions needed to move towards such an envisioned system. Selected papers address transition in production de Olde et al 2017;Grin 2012;Hoppe et al 2016;Pant et al 2014), processing Rosin et al 2017), consumption (Vinnari and Vinnari 2014;Vittersø and Tangeland 2015) or in the whole food system Gorissen et al 2018;Kuhmonen 2017;van Gameren et al 2015). Other papers adopt a wider approach and deal with bioeconomy (Hansen and Bjørkhaug 2017) or water-energy-food nexus .…”
Section: Transition Managementmentioning
confidence: 99%
“…Van Gameren et al (2015) highlighted that socio-political configurations, institutional contexts and governance arrangements influence the nascent local food systems in Belgium and, consequently, sustainable food consumption transitions. Therefore, they put Gorissen et al (2018) Urban food system Belgium Grin (2012) Dutch agriculture in the post-World War II The Netherlands Halbe et al (2015) Water-energy-food nexus Cyprus Hansen and Bjørkhaug (2017) Bioeconomy Norway Hoppe et al (2016) Phosphorus and nitrogen management Multi-country (The Netherlands and Finland) Kuhmonen (2017) Potential of futures images in food system transition Finland Long et al (2018) Food and beverage industry The Netherlands Pant et al (2014) Transformation in subsistence farming Nepal Rosin et al (2017) Sustainable wine production New Zealand van Local food systems Belgium Vinnari and Vinnari (2014) Plant-based diets Undefined Vittersø and Tangeland (2015) Organic food Norway governance, politics and institutions at the centre of the debate on sustainable consumption. Hoppe et al (2016) addressed resource politics in their critical analysis of the governance of phosphorus and nitrogen systems in Finland and the Netherlands.…”
Section: Transition Managementmentioning
confidence: 99%
“…This strengthens the incremental innovations within the existing structure keeping the overall structure of existing industries intact. Previous studies also showed that the transition towards sustainable bioeconomy systems are prevented by several barriers, such as market failures, lack of directionality, policy coordination, institutions, capabilities, and infrastructure (Hoppe et al 2016).…”
Section: Conceptual Background For Transition Framework and Applications To Forest Sectormentioning
confidence: 99%